The sweet magnolias cookbook ebook More than 150 favorite southern recipes. - Woods, Sherryl (Sweet Magnolias., 2012)
Fill your home with the freshly baked scent of luscious apple pie, the sizzle of peachy grilled chicken or the beckoning aroma of juicy roast lamb, all brought to life in this charming collection of recipes. New York Times bestselling author Sherryl Woods invites you into the world of Serenity, South Carolina, where good food and good friends await. Based on her beloved Sweet Magnolias series, this gorgeous cookbook is full of Southern classics and heartwarming stories of friendship and fun. Join Dana Sue Sullivan, a popular character and Southern cook herself, as she shares her favorite down-home recipes as well as secrets, stories and small-town gossip from the world of the Sweet Magnolias! Whether you're making flaky, buttery, too-good-to-be-true biscuits, or spicy seafood gumbo, the 150 recipes found in these pages will bring your family and friends together to celebrate the comforts of home. From legendary margarita nights to indulgent Sunday brunches to heartening holiday meals, every recipe in this book is sure to infuse your life and your kitchen with the warmth of the South and the comfort of good food.